Fenomenologi Revaluasi Aset di Sektor Publik - Witang Pranestianegara; Rida Perwita Sari (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to explore a problem or issue raised, namely the revaluation of assets in the public sector. The phenomenology used in describing the experiences of state asset managers and financial reports focuses on asset evaluation activities to find the essence of the experiences they face from their point of view. This research was conducted on 3 (three) Technical Implementation Units of the East Java Regional Transportation Human Resources Development Unit with the status of a Public Service Agency (BLU) Work Unit. The data used is primary data from direct interviews with informants supported by audited 2015-2021 financial report data at the East Java level. The informants used are asset managers and the preparation of financial reports from Politeknik Perkeretaapian Indonesia Madiun, Politeknik Penerbangan Surabaya dan Politeknik Pelayaran Surabaya. The results of the study found that the revaluation of assets resulted in an increase in the value of fixed assets, especially in the land account which experienced an increase (appreciation). This increase in value affects the value of fixed assets in the Government's balance sheet financial statements. Through the Revaluation of State-Owned Assets (BMN) it encourages improvements in the administration and management of BMN assets, namely being able to determine the cost of maintaining assets appropriately in the post-revaluation period in order to be effective. The results of the revaluation of state-owned assets still require supervision and control in order to continue to provide maximum impact in optimizing the function of assets in order to increase state revenues.